Ingeniería del Software I: Requerimientos y Modelado del Software. - Celi-Párraga, Ricardo Javier; Boné-Andrade, Miguel Fabricio; Mora-Olivero, Aldo Patricio; Sarmiento-Saavedra, Juan Carlos (Editorial Grupo AEA, 2024)
In this book the fundamentals of software engineering were investigated and the basic concepts of software and the processes for the creation of software were documented, it was also documented how to carry out an analysis of software requirements, what are the types of requirements, how to obtain them, document them, validate them and model them by means of different types of diagrams. The objective of this book is to apply the concepts and theories of management for the creation of quality software through the different methodologies, techniques and tools of software engineering so that the information systems professional is able to manage efficiently and in ethical and responsible environments projects immersed in the creation of software. Several books were investigated and a compendium of the most important parts was made and it was concluded that software engineering provides several methodologies for software development and several models for software design that the professional can use depending on the different needs or different situations or projects to develop.